Homeostatic Changes in GABA and Glutamate Receptors on Excitatory Cortical Neurons during Sleep Deprivation and Recovery - del Cid-Pellitero, Esther; Plavski, Anton; Mainville, Lynda; Jones, Barbara E. (Frontiers in Systems Neuroscience, 2017)
Neuronal activity is regulated in a homeostatic manner through changes in inhibitory GABA and excitatory glutamate (Glu) AMPA receptors (Rs). Using immunofluorescent staining, we examined whether CaMKIIα-labeled (+) excitatory neurons in the barrel cortex undergo such homeostatic regulation following enforced waking with associated cortical activation during the day when mice normally sleep the majority of the time. Sleep deprived mice were prevented from falling asleep by unilateral whisker stimulation and sleep recovery mice allowed to sleep freely following deprivation. In parallel with changes in c-Fos reflecting changes in activity, (β2-3 subunits of) GABAA Rs were increased on the membrane of CaMKIIα+ neurons with enforced waking and returned to baseline levels with sleep recovery in barrel cortex on sides both contra- and ipsilateral ¬to the whisker stimulation. The GABAAR increase was correlated with increased gamma electroencephalographic (EEG) activity across conditions. On the other hand, (GluA1 subunits of ) AMPA Rs were progressively removed from the membrane of CaMKIIα+ neurons by (Rab5+) early endosomes during enforced waking and returned to the membrane by (Rab11+) recycling endosomes during sleep recovery. The internalization of the GluA1Rs paralleled the expression of Arc, which mediates homeostatic regulation of AMPA receptors through an endocytic pathway. The reciprocal changes in GluA1Rs relative to GABAARs suggest homeostatic down-scaling during enforced waking and sensory stimulation and restorative up-scaling during recovery sleep. Such homeostatic changes with sleep-wake states and their associated cortical activities could stabilize excitability and activity in excitatory cortical neurons.